A rare case of intracranial Castleman disease - K. A. Sulin; K. A. Chizhova; N. K. Samochernykh; I. Yu. Belov; I. A. Makarov; L. B. Mitrophanova; D. A. Gulyaev (Сибирский онкологический журнал)
Introduction. Castleman disease (CD) is a rare lymphoproliferative disorder also known as angiofollicular lymph node hyperplasia or giant lymphoid hyperplasia. CD is considered unicentric in the presence of a single focus and if the clinical picture is represented by multiple lymphadenopathy and systemic manifestations, it is considered multicentric. Manifestation of the disease by the occurrence of a focus that mimics a tumor of the meninges or brain is extremely rare, only 20 cases are known including the one presented in our article. The main treatment for localized forms is surgical resection. Our observation is devoted to a rare variant of intracranial CD. Description of the clinical case. Woman, 35 years old, was admitted to the clinic with complaints of recurrent headache of moderate intensity of a diffuse nature and difficulty in counting and writing. A month before hospitalization a single generalized epileptic seizure occurred. In the clinical picture at the time of admission, Gerstmann-Schilder syndrome was noted which topically corresponded to the lesion of the right parietal lobe. MRI of the brain with contrast enhancement showed pathological infiltration in the structure of the right parietal bone, the presence of a massive paraosseous component that spread intracranially with compression of the right parietal lobe, and moderately pronounced perifocal edema. The neoplasm was removed totally with a fragment of the dura mater (DM). The plastic of DM was performed with a vascularized periosteal flap and one-stage plastic of the skull defect with a titanium implant. According to histological and immunochemical studies, as well as additional examinations, a diagnosis of unicentric CD was established. According to the results of the control MRI of the brain with contrast enhancement after 3, 6 and 12 months, data for relapse were not revealed. The patient currently does not report any symptoms of the disease. Conclusion. Intracranial unicentric CD is a benign disease amenable to radical surgical treatment and does not require further adjuvant therapy. Despite the complexity of differential diagnosis between CD and meningiomas, the primary treatment strategy remains the same in all cases: total surgical removal.